Produk Fermentasi Rumen dan Produksi Protein Mikroba Sapi Lokal yang Diberi Pakan Jerami Amoniasi dan Beberapa Bahan Pakan Sumber Energi - Novita Hindratiningrum; Muhamad Bata; Setya Agus Santosa (Agricultural Faculty, 2011)
Products of rumen fermentation and protein microbial of dairy cattle feed with rice bran ammonization and some feedstuffs as an energy sourcesABSTRACT. This study aims to examine the energy sources of feed ingredients that can increase the production of Volatile Fatty Acids (VFA), N-NH3, microbial protein synthesis, total gas production and metabolic energy. The material used is as a source of rumen fluid inoculum from Frisian Holstein cows (FH) females, amoniasi rice straw, salt, mineral mix brand